Benzodiazepine use in Spain: risks and perspectives on the current situation and proposals for their rational use - Roncero, Carlos; Armenteros, Lorenzo; Bellido-Cambrón, Carmen; Bonilla-Guijarro, Amparo; Gómez-Cibeira, Emilio (Frontiers in Pharmacology, 2025)
Benzodiazepines are among the most widely prescribed treatments for insomnia, and can have positive effects on sleep when used for a maximum of 4 weeks. However, benzodiazepines disrupt sleep architecture, and their long-term use leads to negative outcomes, including impairments in memory and attention, increased risk of falls (particularly in the elderly) and car accidents, dependence, and addiction. In addition, stopping benzodiazepines after long-term use can result in severe withdrawal symptoms. Spain is one of the countries with the most widespread benzodiazepine use. A multidisciplinary approach is crucial for the treatment of insomnia and for preventing benzodiazepine overuse/misuse. The present study provides an updated overview of the epidemiology and use of these drugs in vulnerable populations (adolescents, older adults and people with mental disorders). We also describe deprescribing strategies used in clinical practice and present two case studies to exemplify the complexities of benzodiazepine withdrawal observed in our practice. Finally, proposals are provided for the rational use of benzodiazepines in Spain, targeted to the general population, healthcare professionals, and regulatory authorities, in order to improve the clinical management of insomnia.